Research of banks participation in crediting the needs of innovative development of industry in Ukraine - Zavadska, Diana (Technology audit and production reserves, 2018)
The object of research is the results of the impact of bank lending on the processes of innovative development of industrial enterprises and the economy of Ukraine. One of the most problematic places is the low level of innovation, innovation activity of Ukrainian industrial enterprises and the economic efficiency of the general investment potential of Ukraine. The slowdown in economic growth also causes a weak and inverse relationship between the processes of innovative development of the country’s economy and long-term bank loans. The absence of a significant effect of long-term bank loans on the processes of modernization and changes in the net financial result of a group of domestic industrial enterprises is attributed to unfavorable factors in the work. The methods of a systematic approach, comparison, correlation analysis, non-parametric statistics, tabular and graphical presentation of the results are used. This allows the author to prove the systemic nature of the negative trends in changes in the innovative development of the economy, due to the general principles of the organization of the socio-economic activities of Ukraine. The results show that one of the main destabilizing factors for development of production and financial stability of industrial enterprises is the low level of profitability of operating activities and above the critical level of depreciation of fixed assets. The peculiarity of financing innovation activity is the irrational structure of the formed sources, where: own funds – 84.49 %; state budget funds – 2.49 %; local budget funds – 1.05 %; funds of domestic investors – 2.96 %; funds of foreign investors – 1.18 %; bank loans – 6.52 %; other funds – 1.26 %. This has a negative effect on the reproduction cycle and actualizes the need to use a bank loan to partially solve the problems of financial support for the restructuring of enterprises in particular and the innovative development of the country as a whole. Using the example of a group of industrial enterprises, it is proved that the increase in net profit is ensured by the increase in capital investment in progress, which is accompanied by an increase in long-term bank loans. On the basis of empirical generalizations, measures are defined to enhance the stimulation of banks’ lending on technological development of the national industry. This is ensured by the practical implementation by the state of a program-target planning method based on targeted management and financing, creating a system of interaction between state and private institutions, direct and venture capital funds, national long-term money and derivatives markets. The implementation of a system of measures will contribute to the creation of jobs, the implementation of infrastructure and innovative projects.